2011
DOI: 10.1016/j.jcrs.2010.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Combined correction of sphere and astigmatism using the light-adjustable intraocular lens in eyes with axial myopia

Abstract: The light-adjustable IOL reduced postoperative spherical and cylindrical errors of up to 2.00 D. Postoperative refractive errors were successfully corrected, and there was a significant improvement in UDVA with concomitant maintenance of CDVA. The achieved refractive change was stable after the adjustment and lock-in procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 20 publications
(19 reference statements)
0
9
0
2
Order By: Relevance
“…With appropriate light delivery settings, Light Adjustable Lenses (LAL) are attempt, at least in part, to address this issue on stable etasia, since this post-insertion method for the correction of refractive errors has been used successfully to correct astigmatism after cataract surgery (Hengerer et al, 2011, Lichtinger et al, 2011, Sandstedt et al, 2006, Schwartz et al, 2001). Topo-guided phototherapeutic keratectomy (PTK) has also been proposed after corneal collagen cross-linking to both stabilize the corneal ectasia and reduce the residual ametropia and other relevant HOA (Krueger et al, 2011, Kymionis et al, 2011.…”
Section: Additional Considerations 41 Optical Aberrations Induced Bymentioning
confidence: 99%
“…With appropriate light delivery settings, Light Adjustable Lenses (LAL) are attempt, at least in part, to address this issue on stable etasia, since this post-insertion method for the correction of refractive errors has been used successfully to correct astigmatism after cataract surgery (Hengerer et al, 2011, Lichtinger et al, 2011, Sandstedt et al, 2006, Schwartz et al, 2001). Topo-guided phototherapeutic keratectomy (PTK) has also been proposed after corneal collagen cross-linking to both stabilize the corneal ectasia and reduce the residual ametropia and other relevant HOA (Krueger et al, 2011, Kymionis et al, 2011.…”
Section: Additional Considerations 41 Optical Aberrations Induced Bymentioning
confidence: 99%
“…Salgado et al 9 reported a reduction in spherical equivalent from C0.39 D before the adjustments to À0.07 D 6 months after the adjustments. A more recent study of 21 eyes by Hengerer et al 10 showed positive results at 1 year postoperatively: 96% of eyes were within G0.50 D of the intended refraction and 81% were within G0.25 D. Winkler von Mohrenfels et al 11 showed that such refractive accuracy converts to good visual outcomes, reporting a mean UDVA of 1.02 in eyes that had a light-adjustable IOL.…”
Section: Discussionmentioning
confidence: 98%
“…The IOL is manufactured in 0.50 D increments from 17.00 to 24.00 D and in 1.00 D increments from 10.00 to 17.00 D and 24.00 to 30.00 D. After implantation of the IOL, the spherical and cylindrical power can be adjusted in the range of G0.25 to 2.00 D by irradiating the lens with a targeted dose of profiled light delivered using a digital light-delivery device (Carl Zeiss Meditec AG). [4][5][6][7][8][9] The IOL is implanted in the posterior chamber after phacoemulsification through a 2.75 mm superior clear corneal tunnel incision and a 5.00 to 5.50 mm capsulorhexis using standard surgical techniques. After a period of postoperative refractive stabilization, typically 10 to 21 days, the patient returns for examination and refraction by the surgeon to determine whether adjustment in spherical and cylindrical power is required.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Recently, prospective studies of myopic corrections and residual hyperopic corrections were published. [5][6][7][8][9] The light-adjustable IOL is based on the inclusion of a proprietary photoreactive silicone macromer within a medical-grade silicone polymer matrix. Selective irradiation of the implanted light-adjustable IOL using a light-delivery device to deliver targeted doses of ultraviolet (UV) light (365 nm) produces modifications in the IOL curvature, resulting in a predictable spherical and/or cylindrical power change postoperatively.…”
mentioning
confidence: 99%